THE EFFECT OF PRICE AND SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH INDIHOME CUSTOMER SATISFACTION AT PT. INDONESIA TELKOM MAKASSAR WITEL STO MATTOANGIN - jefri barung tappi; Otto R. Payangan; Nuraeni Kadir (The Scientia Journal of Economics Issues, 2023)
This study aims to determine the effect of price and service quality on customer loyalty through indihome customer satisfaction at PT. Telecommunications Indonesia Witel Makassar STO Mattoangin. This research is a quantitative research, the data used is primary data, namely data obtained from distributing questionnaires to the research object. The sampling technique used Nonprobability Sampling with a total sample of 390 respondents. The analytical method used in this study is regression analysis through SPSS version 26. The results of this study indicate that (1) price has a positive and significant effect on customer satisfaction; (2) service quality has a positive and significant effect on customer satisfaction; (3) price has a positive and significant effect on customer loyalty; (4) service quality has a positive and significant effect on customer loyalty; (5) customer satisfaction has a positive and significant effect on customer loyalty; (6) customer satisfaction as an intervening variable capable of influencing prices on customer loyalty; (7) customer satisfaction as an intervening variable cannot influence service quality on customer loyalty.